A COMPARATIVE STUDY OF ANTI-NOCICEPTIVE ACTIVITY OF CURCUMA LONGA LINN. WITH THAT OF IBUPROFEN IN EXPERIMENTAL ANIMALS - PHUKAN, SWOPNA; DAS, SAHELI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The aim of the study is to evaluate and compare the analgesic activities of Curcuma longa Linn. in the experimental animals. Methods: The present study was conducted in the Department of Pharmacology, Gauhati Medical College and Hospital, after getting approval from the Institutional Animal Ethics Committee (No MC/68F/2009/MAR-19/02). Healthy rodents weighing between 150 and 200 g were selected and randomly divided into five groups, each group consisting of six animals. Tail-flick analgesiometer was used to assess the analgesic activity of C. longa Linn. and ibuprofen in the experimental animals. Appropriate statistical analyses like Student’s t-test were used to analyze the data. Results: The mean reaction time (s) was prolonged on gradually increasing the dose of C. longa Linn. from 200 to 400 mg/kg. At 400 mg/kg dose C. longa Linn. produced similar analgesic activity as compared to ibuprofen (30 mg/kg). Conclusion: From the study, it can be concluded that curcumin has the capacity to attenuate pain, and when administered in high doses, may produce similar activity as other conventional NSAID’s.